2019
DOI: 10.1016/j.jvacx.2019.100020
|View full text |Cite
|
Sign up to set email alerts
|

Sense & sensibility: Decision-making and sources of information in mothers who decline HPV vaccination of their adolescent daughters

Abstract: Highlights A good first and overall impression is key to vaccine uptake. GP recommendation increases the likelihood of HPV vaccination. Mothers with a higher educational level are likely to accept HPV vaccination. Fathers taking part in the decision increases the likelihood of HPV vaccination. Valuing news and media stories decreases the likelihood of HPV vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 25 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…A study dealing with mothers’ decisions for not allowing their adolescent children to be vaccinated against human papillomavirus (HPV) reported an overall response rate of 54%. 16 Their higher response rate may be explained by the topic, which had extensive media coverage in Denmark at that time. Their response rates for the 20–29 years old and 30–39 years old were 14% and 17% larger than ours for these age groups, but their response rate for mothers who were working was 5% higher than the response rate for our working individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A study dealing with mothers’ decisions for not allowing their adolescent children to be vaccinated against human papillomavirus (HPV) reported an overall response rate of 54%. 16 Their higher response rate may be explained by the topic, which had extensive media coverage in Denmark at that time. Their response rates for the 20–29 years old and 30–39 years old were 14% and 17% larger than ours for these age groups, but their response rate for mothers who were working was 5% higher than the response rate for our working individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Parents have reported receiving stories about the harms of HPV vaccines on social media and news media, while stories on the prevention of HPV disease occurred in conversations (12). In one study, mothers who first learned about HPV vaccines through social media tended not to vaccinate daughters, while those first hearing about it from their general practitioner vaccinated them (36). There have been calls for efforts to improve accurate HPV content on social media and correct misinformation (37)(38)(39)(40)(41) to improve clinical encounters on HPV vaccines (32).…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing use of robots may worsen the problem [43]. Health professionals should therefore acknowledge the threat and engage with social media [23,44], especially following the revelation that mothers who declined HPV vaccination sought information on social media rather than from their general practitioner [45]. Indeed, Betsch et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing use of robots may worsen the problem [43]. Health professionals should therefore acknowledge the threat and engage with social media [23,44], especially following the revelation that mothers who declined HPV vaccination sought information on social media rather than from their general practitioner [45]. Indeed, Betsch et al [46] showed that accessing vaccine-critical websites increases the perception of the risk of vaccinating and decreases the perception of the risk of omitting vaccinations.…”
Section: Discussionmentioning
confidence: 99%